Estudo numérico de acopladores asimétricos aplicados na implementação de portas lógicas totalmente ópticas - Almeida, José Silva de (2006)
In this work, we presented an investigation numerical of the transmission and switching fundamental solitons in nonlinear double couplers, constituted for fibers optics with index decreasing dispersion (DDF). Logic Gates Optical are proposed, based in the use of a asymmetric nonlinear directional double coupler (NLDC) of fiber optic and with one of the guides operating with profile of decreasing dispersion. For such end, we obtained the transmission characteristics and, therefore after, made an analyze of the Extinction Ratio and compression factor. We investigated the acting of the coupler proposed operating in the regime solitonic, using ultra-short pulses with 2 ps of width. With the model proposed for the device, got to implement logic gatesAND, OR, XOR and NOT for several phases.